The Influence of Financial Literacy on Interest in Conducting Online Financing in Employees with Religiosity Variables - Munauwaroh, Siti; Mahardika, Swadia Gandhi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study aims to determine the effect of Islamic financial literacy on the interest in conducting Islamic online financing with religiosity as a moderating variable on employees of the Nabil Husein Islamic Boarding School. This study uses a quantitative method with a population of all Islamic boarding school employees and a sample size of 40 respondents. The data collection technique was carried out by distributing questionnaires directly to the office of the Nabil Husein Islamic Boarding School. Data analysis was carried out using the outer model analysis tool, inner model, and hypothesis testing to test the relationship between variables. The results of the study indicate that Islamic financial literacy has a significant effect on the interest in Islamic online financing. This means that the higher the Islamic financial literacy, the higher the individual's interest in using Islamic-based online financing services. However, the religiosity variable does not have a positive effect and is unable to moderate the effect of Islamic financial literacy on this interest. This shows that the level of employee religiosity does not strengthen the relationship between Islamic financial literacy and interest in Islamic online financing. These findings provide implications for Islamic financial institutions to focus more on improving Islamic financial literacy in order to encourage interest in Islamic online financing products.